Synthesis of Ni(II), Cu(II) and Co(II) complexes with new macrocyclic Schiff-base ligand containing dihydrazide moiety: Spectroscopic, structural, antimicrobial and antioxidant properties. (September 2017) - Gull, Parveez; Babgi, Bandar A.; Hashmi, Athar Adil
Abstract: In this study, the macrocyclic Schiff base ligand (L) derived from 1, 4-dicarbonyl-phenyl-dihydrazide and glyoxal (2:2) and its Ni (II), Cu (II) and Co(II) complexes were synthesised and were characterised by elemental analyses, FTIR, UV–Vis., mass and 1 H NMR. The ligand (L) behaves as a tetradentate ligand and coordinates to the metal ions via the nitrogen atoms and the complexes have the mononuclear structures. The synthesised compounds were evaluated for their inhibition potential against bacterial and fungal strains and the assay indicated that the metal complexes exhibited a remarkable antibacterial and antifungal activity against these tested strains. In addition, the antioxidant activity of the compounds was also studied through scavenging effect on DPPH radicals with the copper complex showing enhanced antioxidant activity than other metal complexes. Graphical abstract: Highlights: Preparation of Ni(II), Cu(II) and Co(II)complexes of the new macrocyclic schiff's base ligand. Elemental analysis, spectral characterization of the ligand and its complexes. IR spectrum of the ligand indicates the coordination of the azomethine nitrogen atoms. The synthesised compounds were screened in vitro against different microbes as growth inhibiting agents. The complexation led to a remarkable increase in antimicrobial activity.